Effect of various nerve decompression procedures on the functions of distal limbs in streptozotocin-induced diabetic rats: Further optimism in diabetic neuropathy - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2003)
It is known that diabetic neuropathy is the result of endoneurial edema caused by various biochemical reactions triggered by hyperglycemia. This sequence of events can cause cessation of circulation at the perineurial level, or the tough layer, which is not resilient enough to spread intraneural pressure. Internal and external limiting structures create a double crush phenomenon to the nerve structure. Decompression of the nerve trunk at separate levels is one of the adjuncts to the overall treatment plan for diabetic neuropathy. In this study. the right sciatic nerves of 30 rats with streptozotocin-induced diabetes were used; three groups were created. In the control group, the sciatic nerves were explored and dissected only. In group II, tarsal tunnel release was performed and accompanied by epineurotomy of the sciatic nerve and its peroneal and tibial extensions. In group III, in addition to the procedures performed in group II, perineural sheaths, exposed through the epineurotomy sites at both the peroneal and tibial nerves, were incised for decompression of the fascicles. Improvement in diabetic neuropathy was evaluated by using footprint parameters. The last print length values estimated according to the 38-month measure in en is, were 26.1 +/- 0.12 mm in the control group, 23.2 +/- 0.07 mm in group II, and 22.2 +/- 0.1 turn in group III. The toe spread and intermediate toe spread values of the groups were parallel to improvements in print lengths throughout the study. The best improvement was observed in the perineurotomy group. Finally, an electron microscopic study revealed variable degenerative changes in all groups, but they were milder in groups II and III. This experimental study reveals that adding internal decompression to external release doubled the effect in reducing derangement in the sciatic nerves of the rats and, in the authors' opinion, offers cause for further optimism in the treatment of diabetic neuropathy.
Keywords: PERIPHERAL-NERVES; SCIATIC-NERVE; COMPRESSION; MELLITUS